The Influence of Auditor Individual Factors to the Time it Takes in Detecting Fraud - Angelique, Valencia; Silalahi, Jesica Hasianna; Saragih, Rio Lambardo; Sari, Martdian Ratna; Maulana, Noveri (Association of Certified Fraud Examiners Indonesia Chapter, 2024)
ACFE Indonesia 2019 shows that fraud can be found or detected within 12 months. This indicates that there are factors that prevent the fraud from being detected quickly, such as individual auditor factors that play a role in detecting the fraud. The novelty of this research is to focus on individual factors including auditor’s experience, independence, competence and personality type. This research is a quantitative study using surveys, with internal auditors, external auditors and KAP partners as respondents. Results of this study found that factors that greatly influence auditor’s ability to detect fraud are auditor’s experience, independence, competence. Meanwhile, personality has no influence on auditor’s ability to detect fraud. Results of this study can contribute to the association of public accountants in evaluating the criteria for expert auditors who are given permission to conduct investigative audits. It is expected that KAPs (Public Accounting Firms) will offer resources and opportunities to enhance the competence and independence of their auditors.